Elections Legal Entity As rescue efforts Revolving Fund Program PNPM Mandiri Urban and Rural - HARYADI .; LAELI BUDIARTI; DIJAN RAHAJUNI; SRI RESTARI; REFIUS P. SETYANTO (Jurnal Bisnis Manajemen, 2015)
The aim of this research is to analyze the performance of PNPM Mandiri Program and identify the desirability ofstakeholder in managing revolving fund of PNPM Mandiri after the end of this program in Banyumas Regency. Informanas source of the data consist of PNPM organizer, facilitator, and the community who received revolving fund. We usequalitative and quantitative techniques to analize the data. Our analysis shows that the amount of the fund is morethan a hundred billion. They have been revolving and need to manage by legal entity organization. Meanwhile, thedesirability of the stakeholder of PNPM Mandiri especially PNPM Organizer is different. Some people want the publiccorporation as the legal entity to manage the fund, but the others want cooperation.Keywords: PNPM Mandiri, Revolving Fund, Cooperation, public corporation.